“HEALTH IN ALL POLICIES” APPROACH AND ITS IMPLEMENTATION - Milenković, Marko; Sjeničić, Marta (Glasnik Advokatske komore Vojvodine, 2020)
Public health policy covers a much wider area than healthcare. The Health in All Policies (HIAP) approach implies that health issues are taken into consideration in decision making in different sectors that have health aspects, such as agriculture, land use, urban planning, housing, transport, public security, education and many others. The principle has been applied at EU level to cross-sectoral cooperation towards the achievement of common goals from the 2006 Finnish EU Presidency, and has since become increasingly present in relevant documents, both at supranational level and in many European countries.